Konseling Sufistik: Harmonisasi Psikologi dan Tasawuf dalam Mewujudkan Kesehatan Mental - Zamzami Sabiq ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2016)
Mental Health engenders harmony, tranquility, welfare, and peace of the soul. Mental health can be realized if we comprehend the nature of human being as individual, social being, and religious being. This study attempts to examine sufistic counseling as a result of the harmonization between psychology and sufism whose role is strong enough for the realization of mental health. Human being perspective in psychology and sufism were also presented to gain a better and more comprehensive understanding of human nature. Using library research of relevant literature as the method, this study concludes that sufi counseling could be a bridge to harmonize between psychology and sufism. It also could be directed to realize mental health in individual level. In addition, sufism provides a typical pattern for the development of counseling and it has a great opportunity to give its own color for counseling trend in the modern era.